White and Black in “Sigumo” by Boris Akunin - O. A. Selyunina (Научный диалог)
The results of analysis of colour vocabulary in the story by Boris Akunin “Sigumo” are presented. The relevance of the study is due to the importance of the category of “colour” for the human worldview and individual author’s picture of the world. The paper provides a brief overview of linguistic literature devoted to the study of colour vocabulary. The author proceeds from the fact that the vocabulary with the meaning of colour in an art work reflects the originality of the colour picture of the artist’s world and, therefore, is an important feature of the holistic artistic picture of the world. The novelty of the research lies in the choice of the product for analysis. The facts of using colour vocabulary in the text of the story by Boris Akunin “Sigumo” are the material for the study. Colour vocabulary is classified by lexical-grammatical feature and by the nomination object. Special attention is paid to colour lexis within the lexical-semantic group of “white” and “black colour” as the most important and most frequent in the colour pattern of the studied art work. It is argued that colour contrast is one of the dominant principles of constructing the analyzed literary text. The author concludes that B. Akunin shows that clear boundaries between black and white does not exist in the same way as there is no clear boundary between good and evil, ugliness and beauty, the Western and Eastern worlds.